Study on removal of heavy metals (As, Pb) in agricultural soils using Bidens pilosa L. - Huynh, An The; Chen, Yi-Ching (Journal of Degraded and Mining Lands Management, 2025)
This study aimed to assess the capacity of Bidens pilosa L. to absorb heavy metals, specifically arsenic (As) and lead (Pb), in contaminated soil environments, with the goal of laying a foundation for applying phytoremediation techniques to remediate agricultural soils polluted with heavy metals in Vietnam. The findings indicate that B. pilosa L. can thrive in soils contaminated with heavy metals at concentrations up to 700 mg/kg. Additionally, the absorption rates in the roots, stems, and leaves of B. pilosa L. were substantial. At a concentration of 700 mg/kg As, the absorption rates were 66.53% in roots, 20.45% in stems, and 13.03% in leaves. For Pb, at the same concentration, the absorption was 64.41% in roots, 21.27% in stems, and 14.32% in leaves. Moreover, the bioconcentration factor (BCF) and translocation factor (TF) further support the plant's potential. The BCF for As decreased from 0.123 at 0 mg/kg to 0.023 at 700 mg/kg, while the BCF for Pb showed a similar trend, ranging from 0.017 to 0.023 across increasing concentrations. The TF for As dropped from 1.202 at 100 mg/kg to 0.503 at 700 mg/kg, while the TF for Pb ranged from 0.959 to 0.552, indicating limited translocation of metals from roots to aerial parts at higher contamination levels. These results suggest that B. pilosa L. is a promising candidate for phytoremediation of soils contaminated with arsenic and lead, thanks to its ability to accumulate these metals predominantly in its roots, thereby limiting their movement to stems and leaves.